Rapidly reversible acute neurological, renal, and cardiac impairment during malignant hypertension - Giulia Nardi; Silvia Menale; Valentina Scheggi; Niccolò Marchionni (SpringerOpen, 2023)
Abstract Background Malignant hypertension is a model of the rapid changes that a high afterload and renin-angiotensin levels can induce on target organs such as the heart. We present a case of a young man affected by malignant hypertension with multi-organ involvement who showed quick remission after adequate antihypertensive treatment. Case summary A 41-year-old jazz pianist with a family history of coronary artery disease presented to the emergency department for asthenia and epigastric pain, associated with right eye visual impairment. No neurological symptoms. An echocardiogram showed left ventricular hypertrophy with severe impairment of ejection fraction (22%) due to global hypokinesia. There was renal insufficiency (creatinine 2.51 mg/dl, eGFR 34 ml/min, HS Troponin T 127 pg/dl, NT pro-BNP 22,672 pg/ml, CRP 32 mg/L, sodium 129 mEq/L with normal kaliemia. The following day, anterior T wave inversion was observed in the electrocardiogram. At a cardiac magnetic resonance. Concentric hypertrophy of the left ventricle was observed with normal myocardial T1 mapping values (1100 ± 38 ms), ruling out Fabry's disease. There was no obvious myocardial edema at T2 weighted. The viral panel for acute myocarditis resulted in negative. After the exclusion of all possible secondary causes, malignant essential hypertension was the final diagnosis, and additional tests confirmed multi-organ damage. An ophthalmological examination demonstrated hypertensive retinopathy with hemorrhages, cottony exudates, and macular lipid exudation, especially in the right eye. A brain MRI showed small areolas of T2 hyperintensity in the white matter of both cerebral hemispheres, suggestive of chronic microangiopathy, and left nuclear micro lacunar ischemia. The patient was treated with full-dose calcium channel blockers (amlodipine 10 mg), beta-blockers (bisoprolol 10 mg), alpha2 agonists (slow-release clonidine patch), selective a1 blocker (doxazosine 16 mg), and furosemide 50 mg. After the exclusion of renal stenosis and improvement of renal function, Ramipril was added up to a final dose of 10 mg daily. In parallel with the achievement of a satisfactory blood pressure control, visual impairment disappeared with a reduction of retinal ischemic exudates and hemorrhages at the ophthalmological follow-up assessment. At the time of discharge, an echocardiographic re-evaluation confirmed concentric hypertrophy of the left ventricle with markedly reduced wall thicknesses, with a partial recovery in left ventricular ejection function (EF 44%). Six months after discharge, the patient is in good general condition under optimal medical therapy (without furosemide) with normalized blood pressure values (130-140/80 mmHg). At 6 months from discharge, creatinine was only mildly increased (1.5 mg/dl, eGFR 59.5 ml/min) and NT-pro BNP nearly normalized (452 pg/ml). Discussion Malignant hypertension is a cardiovascular emergency and requires immediate and careful intervention to lower blood pressure and reduce organ injury. It is an exclusion diagnosis that can be advanced once the causes of secondary hypertension have been excluded. Remission of organ injury is possible and might be rapid under adequate antihypertensive treatment, but patients require a close follow-up.